2017
DOI: 10.1121/1.4976341
|View full text |Cite|
|
Sign up to set email alerts
|

An experimental study of the wall-pressure fluctuations beneath low Reynolds number turbulent boundary layers

Abstract: A more complete understanding of the physical relationships, between wall-pressure and turbulence, is required for modeling flow-induced noise and developing noise reduction strategies. In this study, the wall-pressure fluctuations, induced by low Reynolds number turbulent boundary layers, are experimentally studied using a high-resolution microphone array. Statistical characteristics obtained using traditional cross-correlation and cross-spectra analyses are complimented with wall-pressure-velocity cross-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 39 publications
7
42
0
Order By: Relevance
“…Numerical simulations have been applied sparingly due to high computational expenses, however, Lee & Sung [82] attempted to characterize the spatial extent of hairpin packets using the same feature extraction technique [20], on a direct numerical simulation of a turbulent boundary layer. They reported hairpin packets in the loglayer, with lengths up to 3δ -4δ, with the overall large-scale motion retaining statistical coherence up to 6δ, which is in good agreement with the extent of cross-correlation and cross-spectrum energy in experimental wall-pressure measurements [11,29,40,50,67].…”
Section: Figure 16supporting
confidence: 66%
See 2 more Smart Citations
“…Numerical simulations have been applied sparingly due to high computational expenses, however, Lee & Sung [82] attempted to characterize the spatial extent of hairpin packets using the same feature extraction technique [20], on a direct numerical simulation of a turbulent boundary layer. They reported hairpin packets in the loglayer, with lengths up to 3δ -4δ, with the overall large-scale motion retaining statistical coherence up to 6δ, which is in good agreement with the extent of cross-correlation and cross-spectrum energy in experimental wall-pressure measurements [11,29,40,50,67].…”
Section: Figure 16supporting
confidence: 66%
“…Re θ = 1,886 and Re θ = 2,593, from a study by Van Blitterswyk & Rocha [67], are shown in Fig. 4.9a and Fig.…”
Section: Streamwise Cross-spectrum and Coherence Lengths Of Wallpressmentioning
confidence: 97%
See 1 more Smart Citation
“…Smallamplitude vortices may thus still be detected, but with low spatial accuracy. The spatial resolution may be increased using pinhole-mounting, e.g., (Robin et al 2012;Van Blitterswyk and Rocha 2017). This requires a large amount of sensors when measuring pressure over even a moderately large area.…”
Section: Introductionmentioning
confidence: 99%
“…There is therefore a need to not only assess these inconsistencies with experimental methods that cover a wide scope of flow conditions and speeds, but also to clarify the fundamental physical relationship between the turbulent structures within the boundary layer and their contributions to the pressure fluctuation signature. Carleton University has dedicated resources to this area of research through statistical studies of TBL pressure fluctuation phenomena through experimental measurements in low-speed environments using the Medium Speed Aeroacoustic Wind Tunnel Facility (MSAWT) [16,17]. The next phase of this research initiative, and the ultimate focus of this thesis, involves expanding Carelton's capabilities through the design and fabrication of an experimental platform capable of studying the nature of surface pressure fluctuations at a wide range of subsonic flow speeds; including those that are more representative of typical cruise flight conditions of general business and commercial aircraft.…”
Section: Motivationmentioning
confidence: 99%